Biodiversitas sumber daya ikan di hulu Sungai Opak [Biodiversity of fisheries resources in upstream of Opak River] - Djumanto Djumanto; N. Probosunu (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2011)
Biological species diversity in natural habitats is a source of germplasm, which is invaluable. The purpose of this research was to determine the biotic diversity of fishes in upstream of Opak River. Fish sampling was done by using electrofishing. Each sampling was done for one hour along the river as far as about 1 km. All samples were preserved in 5% formaldehyde. Each sample was identified and measured their length and weight. Data were analyzed descriptively in the form of tables and figures. Biotic diversity was analyzed by biology index. The results showed that number of fish found at some 12 species, namely Channa striata, Clarias batrachus, Monopterus albus, Nemacheilus fasciatus, Nemacheilus sp., Oreochromis sp., Poecilia latipinna, Poecilia reticulata, Puntius binotatus, Barbonymus gonionotus, Oreo-chromis niloticus, and Xiphophorus helleri. The most dominant of catching was composed of barred loach (N. fas-ciatus), spotted barb (P. binotatus), and guppy (P. reticulata). Total catch of fish per hour ranged from 111.7 g and 701.7 g. There was inverse relationship between prey and predatory fish population. As the biomass of predatory fish was very low, the biomass of preyfish was very high, which was dominated by small fish of low value, vise verca.The diversity ranged from 1.44 to 1.93, homogeneity ranged from 0.60 to 0.82, the dominance ranged from 0.19 to 0.39. Relatively low diversity index showed the fishing intensity was very high.The fish diversity in environmental was in the category of being depressed. AbstrakKeanekaragaman hayati suatu spesies di habitatnya merupakan sumber plasma nutfah yang sangat berharga. Tujuan penelitian untuk mendapatkan informasi keragaman biotik ikan yang habitatnya di hulu Sungai Opak. Pengambilan con-toh ikan dilakukan dengan kejutan (electrofishing). Setiap pengambilan contoh ikan dilakukan selama satu jam menyusuri sungai sejauh sekitar 1 km. Semua contoh ikan diawetkan dalam formalin 5%. Setiap contoh ikan diidentifikasi dan diukur panjang dan ditimbang bobotnya. Data dianalisis secara deskriptif dalam bentuk tabel dan gambar. Keanekaragaman biotik dianalisis dengan indeks biologi. Hasil penelitian menunjukkan bahwa jumlah ikan yang ditemukan di hulu Sungai Opak sebanyak 12 spesies, yaitu Channa striata, Clarias batrachus, Monopterus albus, Nemacheilus fas-ciatus, Nemacheilus sp., Oreochromis sp., Poecilia latipinna, Poecilia reticulata, Puntius binotatus, Barbonymus go-nionotus, Oreochromis niloticus, dan Xiphophorus helleri. Hasil tangkapan yang paling dominan terdiri atas uceng (N. fasciatus), wader cakul (P. binotatus), dan ikan seribu (P. reticulata). Hasil tangkapan ikan per jam berkisar dari 111,7 g dan 701,7 g. Ada hubungan terbalik antara mangsa dan populasi ikan predator. Ketika biomassa ikan predator sangat rendah, maka biomassa ikan mangsa sangat tinggi, yang didominasi oleh ikan kecil bernilai rendah, demikian sebaliknya. Keanekaragaman berkisar 1,44-1,93; homogenitas berkisar 0,60-0,82; dan dominansi berkisar 0,19-0,39. Indeks keanekaragaman ikan relatif rendah menunjukkan tekanan dan intensitas penangkapan ikan sangat tinggi.